Numerical simulation on the anti-penetration performance of polyurea-core Weldox 460 E steel sandwich plates. (15th March 2020) - Liu, Qi-Qing; Wang, Shi-Ping; Lin, Xin; Cui, Pu; Zhang, Shuai
Abstract: Polyurea has the characteristic of strong energy absorption capacity, and thus it is considered to be an excellent material for structural protection. Therefore, research on the anti-penetration performance of polyurea-core sandwich plates is of great significance for understanding the mechanism of protection and extending its application. In this paper, the anti-penetration performance of polyurea-core sandwich plates is investigated by using the AUTODYN-2D axisymmetric algorithm. Firstly, the accuracy of the numerical algorithm and the polyurea material model are both validated against the experimental data. On the basis, four different thicknesses (from 8 mm to 20 mm) of the interlayer and seven different initial impact velocities (from 300 m/s to 1100 m/s) are selected to study the anti-penetration performance of the polyurea-core sandwich plates under different conditions. Meanwhile, the comparative numerical cases are also performed using rubber-core sandwich plates. The results show that during the penetration, the polyurea presents obvious self-closing behavior, which increases the ballistic resistance. With respect to the rubber-core sandwich plate, the velocity drop per unit areal density of the polyurea-core sandwich plate, as well as the energy absorption ratio, is always greater. As a result, the polyurea interlayer can significantly improve the anti-penetration performance of the sandwich plate.